2019
DOI: 10.1108/jfc-11-2018-0117
|View full text |Cite
|
Sign up to set email alerts
|

Climbing the corporate ladder: desired leadership skills and successful psychopaths

Abstract: Purpose Many of the characteristics embodied by successful psychopaths, such as superficial charm, cool decisiveness and a grandiose self-worth, are often treated synonymously with corporate leadership qualities. Consequently, it is possible that successful psychopaths are actively being selected for corporate positions as they exemplify the perfect candidate. The purpose of the current study was to determine whether or not the recruitment for positions of higher social status are inadvertently seeking out ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…This helps to explain the outstanding levels of greed, risk taking with other people's money and lack of integrity that characterized employees in the corporate banks involved in the GFC. Findings demonstrated that corporations were seeking the characteristics that are synonymous to the personality traits of the primary psychopath, which would tend to increase the propensity of successful psychopaths being present in the workplace (Hill and Scott 2019).…”
Section: Organizational Antecedentsmentioning
confidence: 99%
“…This helps to explain the outstanding levels of greed, risk taking with other people's money and lack of integrity that characterized employees in the corporate banks involved in the GFC. Findings demonstrated that corporations were seeking the characteristics that are synonymous to the personality traits of the primary psychopath, which would tend to increase the propensity of successful psychopaths being present in the workplace (Hill and Scott 2019).…”
Section: Organizational Antecedentsmentioning
confidence: 99%
“…Primary psychopaths are more likely to go into university to study business (Litten et al , 2020), and this indicates their interest in the material rewards of a corporate career. Once established in organisational roles, their political and networking skills help their further advancement (Kholin et al , 2020) as they look attractive to human relations practitioners (HR because of their appearance and apparent effectiveness (Hill and Scott, 2019), and consequently there are more corporate psychopaths at the top of organisations (Babiak et al , 2010). In senior positions, corporate psychopaths can yield extraordinary power (de Vries, 2012), but they make less effective decisions than other managers do (ten Brinke et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Primary psychopaths are more likely to go into university to study business (Litten et al, 2020), and this indicates their interest in the material rewards of a corporate career. Once established in organisational roles, their political and networking skills help their further advancement (Kholin et al, 2020) as they look attractive to human relations practitioners (HR because of their appearance and apparent effectiveness (Hill and Scott, 2019), and consequently there are more corporate psychopaths at the top of organisations (Babiak et al, 2010) To successfully address existential threats posed by leaders, employee groups need a good level of integration if they are to successfully engage in concerted action to counter those threats (Schein, 1983). However, corporate psychopaths disintegrate groups via their divide and conquer tactics which minimise opposition to the psychopath (Clarke, 2005).…”
Section: Importance Of White-collar Psychopathsmentioning
confidence: 99%
“…One paper performed a content analysis for the inclusion of characteristics prominent in psychopathic personalities (PPDPRCL) on 25 executive job advertisements (Hill & Scott, 2019). The results demonstrated that corporations are seeking applicants with traits synonymous with factor 1 psychopathy, with 96% of adverts seeking those with the affectiveinterpersonal traits associated with psychopathic personality.…”
Section: Corporate Psychopathy and Professional Successmentioning
confidence: 99%
“…Successful psychopathy is most prominently discussed in terms of professional achievement, however, findings surrounding corporate psychopathy or professional success with psychopathic traits demonstrated some conflicting positions. Firstly, there were accounts of individuals with psychopathic traits being more likely to be in senior management positions (Spencer & Byrne, 2016), acquiring professional success (Howe et al, 2014), and corporations seeking out those who exhibit psychopathic traits for executive job positions (Hill & Scott, 2019). However, Boddy (2014) demonstrated that corporate psychopathy was associated with maladaptive workplace behaviours and unfavourable workplace environments.…”
Section: Synthesis Of Major Findingsmentioning
confidence: 99%